SOLUTION OF MULTI-DIMENSIONAL OPTIMIZATION PROBLEMS USING NEWTON'S METHOD (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
One-variable function optimization is one of the simplest optimization problems. However, it occupies an important place in the theory of optimization. The reason is that one-parameter optimization problems are often encountered in engineering practice, and in addition, complex multidimensional widely used in optimization problems.